Germination and Seedling Growth of Some Chickpea Cultivars (Cicer arietinum L.) under Salinity Stress - A.A. Kandil; A.E. Sharief; S.R.H. Ahmed (Journal of Basic & Applied Sciences, 2012)
In order to study the response of some Chickpea (Cicer arietinum L.) cultivars i.e. Giza 1, Giza 2, Giza 3, Giza 3, Giza 4, Giza 195, Giza 531, and Chickpea stand1to germination under salinity concentrations i.e. control treatment, 4, 8, 12, 16, and 20 dSm-1 NaCl and to confirm the seedling growth performance. A laboratory experiment was laid out at Giza Central Seed Testing Laboratory of Central Administration for Seed Certification, Ministry of Agriculture, Egypt. Giza 3 cultivar exceeded other cultivars in germination percentage, germination index, seedling vigor index, shoot length, shoot and root dry weight followed by Giza 1 and Giza 2 cultivars. Giza 2 cultivar recorded highest mean germination time, followed by chickpea stand 1 and Giza 4 cultivars. Giza 195 cultivar exceeded other cultivars in root length and Giza 531 and Giza 1 cultivars surpassed other cultivars in shoot fresh weight. Chickpea stand 1 and Giza 195 cultivars surpassed other cultivars in seedling height reduction and Giza 1, Giza 2, Giza 3, and Giza 4, came in the second rank. However, the lowest percentages of seedling height reduction were obtained from Giza 531 cultivar. Increasing salinity levels from 0 to 20 dSm-1 significantly decreased germination percentage, germination index, seedling vigor index, shoot and root length, shoot and root fresh weight, shoot and root dry weight and relative dry weight. The control treatment recorded highest averages of these characters, vice versa mean germination time and seedling height reduction. Germination index, seedling vigor index, shoot and root length (cm), shoot and root fresh weight (mg), shoot and root dry weight (mg), seedling height reduction % and relative dry weight % significantly affected by the interaction between chickpea cultivars and salinity concentration. Giza 3, Giza 1 and Giza 2 cultivars were more tolerant to salinity and recommended to be used in breeding program for enhancing chickpea cultivation in newly reclaimed soils.